Comparison of Short-Term DAPT and Long-Term DAPT on the Prognosis of PCI Patients: A Meta-Analysis of Randomized Controlled Trials - Jiaxin Yang; Yaodong Ding; Rui Wang; Kexin Wang; Xiaoli Liu; Hua Shen; Yan Sun; Hailong Ge; Zhe Fang (Reviews in Cardiovascular Medicine, 2022)
Background: Dual antiplatelet therapy (DAPT) is the primary medication for patients after percutaneous coronary intervention (PCI). However, the best DAPT duration is still controversial. This systematic review and meta-analysis aims to assess the safety and effectiveness of short-term (3–6 months) DAPT compared to long-term (12 months) DAPT. Methods: We searched PubMed, Embase, Cochrane Library, and Web of Science systematically for all the randomized controlled trials (RCTs) which compared the different strategies for DAPT in patients undergoing PCI within ten years prior to January 2021. Major bleeding and any bleeding were identified as the safe endpoints. All causes of death, cardiac death, myocardial infarction, definite/probable stent thrombosis, target vessel revascularization, and stroke were identified as the efficacy endpoints. The hazard ratio (HR) and 95% confidence interval (CI) in each study were abstracted. Results: Overall, 11 trials and 24,242 patients were included in this meta-analysis with 15-month median follow-up time. Short-term DAPT was related to reduced risks of major bleeding (HR 0.65, 95% CI 0.48–0.89) and any bleeding (HR 0.64, 95% CI 0.53–0.79). No obvious differences in any of the other endpoints were observed. In acute coronary syndrome (ACS) patients with drug-eluting stents (DES), short-term compared with long-term DAPT was related to a decreased risk of major bleeding (HR 0.57, 95% CI 0.37–0.87) without significant increasing in the risks of any bleeding and ischemic endpoints. Furthermore, short-term DAPT followed by P2Y12 receptor inhibitor monotherapy appreciably lowered the risk of major bleeding (HR 0.64, 95% CI 0.42–0.96) and any bleeding (HR 0.58, 95% CI 0.36–0.93). There were no obvious differences concerning death between the different strategies for DAPT. Conclusions: After PCI with DES, short-term DAPT is safer than long-term DAPT, and is not inferior in effectiveness, even in ACS patients. P2Y12 receptor inhibitor monotherapy following short-term DAPT is also related to a decreased risk of bleeding and may be an alternative anti-platelet strategy.